2014
DOI: 10.1038/nature13788
|View full text |Cite
|
Sign up to set email alerts
|

Dietary modulation of the microbiome affects autoinflammatory disease

Abstract: The incidences of chronic inflammatory disorders have increased significantly over the past three decades1. Recent shifts in dietary consumption are believed to have contributed importantly to this surge, but how dietary consumption modulates inflammatory disease is poorly defined. Pstpip2cmo mice that express a homozygous L98P missense mutation in the Pombe Cdc15 homology (PCH) family proline-serine-threonine phosphatase interacting protein 2 (PSTPIP2) phosphatase spontaneously develop osteomyelitis that rese… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
293
0
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 270 publications
(303 citation statements)
references
References 30 publications
(34 reference statements)
8
293
0
2
Order By: Relevance
“…Samples were sequenced on an Ion PGM System (Thermo Fisher Scientific) according to the manufacturer's instructions, and the results were analyzed with the Ion Reporter software Ion 16S Metagenomics Kit analyses module (Thermo Fisher Scientific). Relative proportions of microbial taxa for each sample and the signal-to-noise ratio were assembled as described previously after filtering out singletons (taxa found in only one sample) and low-coverage taxa (those with <20 total reads) (26). Ssignal-to-noise ratios are depicted in heat map plots generated with R software and principal component analyses generated with Ion Reporter software.…”
Section: Germ-free Mouse Experiments Freshly Isolated Bm Cells Frommentioning
confidence: 99%
“…Samples were sequenced on an Ion PGM System (Thermo Fisher Scientific) according to the manufacturer's instructions, and the results were analyzed with the Ion Reporter software Ion 16S Metagenomics Kit analyses module (Thermo Fisher Scientific). Relative proportions of microbial taxa for each sample and the signal-to-noise ratio were assembled as described previously after filtering out singletons (taxa found in only one sample) and low-coverage taxa (those with <20 total reads) (26). Ssignal-to-noise ratios are depicted in heat map plots generated with R software and principal component analyses generated with Ion Reporter software.…”
Section: Germ-free Mouse Experiments Freshly Isolated Bm Cells Frommentioning
confidence: 99%
“…We previously showed that although IL-1a promotes disease in a mouse model of neutrophilic dermatosis, 10 IL-1b drives neutrophil-mediated disease in a mouse model of osteomyelitis. 16,21,22 Previous studies have shown contradictory roles for wildtype and mutant pyrin (harboring mutations associated with FMF) in IL-1b processing and inflammation. 1,4,23e27 Pyrin recently was identified as an inflammasome-forming sensor that responds to Rho inactivation induced by bacterial infections.…”
mentioning
confidence: 99%
“…Modifying the diet is another approach to altering the microbiota, though precise control will be difficult to achieve. Nevertheless, in mice with a genetic alteration that resulted in arthritis and spontaneous development of osteomyelitis that correlated with intestinal outgrowth of Prevotella, a diet rich in fat and cholesterol decreased levels of gut Prevotella, reduced systemic pro-IL-1β, and prevented bone erosion (163). This demonstrates that diet can have a dominant effect over genetic predisposition.…”
Section: R E V I E W S E R I E S : T R a N S P L A N Tat I O Nmentioning
confidence: 93%